Experimental and numerical investigation of transient phenomena in vacuum ejectors. (1st May 2016) - Jafarian, Ali; Azizi, Mohammad; Forghani, Pezhman
Abstract: In the present work the transient behavior of ejectors is explored experimentally and numerically. The main goal is to achieve an appropriate numerical model for predicting transient phenomena in ejectors. To validate the numerical results, an experimental test rig was built up and a set of experiments was performed. Results showed a good agreement between experiments and numerical simulations and the average deviation of about 16 percent was achieved. Furthermore, employing the validated numerical model a vacuum steam ejector was simulated numerically. Two different linear motive flow pressure profiles were applied to simulate the ejector performance. Results showed that as the slope of the motive flow pressure profile increases as much as twice, the maximum flow rate of suction increases by 40% and the corresponding incidence time decreases. Highlights: We proposed a numerical approach to simulate the transient behavior of ejectors. A set up was built up and the numerical approach was validated experimentally. The more the slope of the motive pressure the more the extremum of suction flow is. A peak point in ejector secondary mass flow rate indicates the chocking phenomenon. Chocking prevents ejector getting higher capacity by increasing motive pressure.